Self-Selected Motivational Music Enhances Physical Performance in Normoxia and Hypoxia in Young Healthy Males - O’Keeffe, Kate; Dean, Jacob; Hodder, Simon; Lloyd, Alex (Frontiers in Psychology, 2021)
Humans exposed to hypoxia are susceptible to physiological and psychological impairment. Music has ergogenic effects through enhancing psychological factors such as mood, emotion and cognition. This study aimed to investigate music as a tool for mitigating the performance decrements observed in hypoxia. Thirteen males (mean ± SD; 24 ± 4 years) completed one familiarisation session and four experimental trials; 1) normoxia (sea level, 0.209 FiO2) and no music; 2) normoxia (0.209 FiO2) with music; 3) normobaric hypoxia (3800m, 0.13 FiO2) and no music; 4) normobaric hypoxia (0.13 FiO2) with music. Experimental trials were completed at 21°C with 50% relative humidity. Music was self-selected prior to the familiarisation session. Each experimental trial included a 15-mins time trial on an arm bike, followed by a 60-sec isometric maximal voluntary contraction (MVC) of the biceps brachii. Supramaximal nerve stimulation quantified central and peripheral fatigue with voluntary activation (VA%) calculated using the doublet interpolation method. Average power output (W) was reduced with a main effect of hypoxia (p = 0.02) and significantly increased with a main effect of music (p = 0.001). When combined the interaction was additive (p = 0.87). Average MVC force (N) was reduced in hypoxia (p = 0.03) but VA% of the biceps brachii was increased with music (p = 0.02). Music reduced subjective scores of mental effort, breathing discomfort, and arm discomfort in hypoxia (p < 0.001). Music increased maximal physical exertion through enhancing neural drive and diminishing detrimental mental processes, enhancing performance in normoxia (6.3%) and hypoxia (6.4%).